Panca Datu Logic Framework for Sustainability Evaluation: Conceptual Development and Three Case Simulations from Bali - Gusti Ngurah Mahardika; Ida Bagus Windia Adnyana; Nyoman Semadi Antara; I Dewa Gede Palguna (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Many public and organizational programs achieve technical success, regulatory compliance, and high budget absorption, yet fail to sustain outcomes once external support ends, as prevailing evaluation frameworks emphasize outputs over sustainability. This gap reflects the absence of an integrated perspective on how institutional conditions shape long-term durability. This paper proposes the Panca Datu Logic Framework (PDLF), where panca denotes “five” and datu foundational elements, as a conceptual guide for sustainability evaluation. Using a conceptual-synthetic approach grounded in abductive reasoning, the framework is illustrated through three case-based simulations in Bali: rabies control, community-based turtle conservation, and waste management programs. The PDLF conceptualizes sustainability as an emergent, non-compensatory property arising from alignment among five domains—legal, human, financial, infrastructure, and culture—with culture positioned as an outcome of systemic coherence. The framework offers an analytical lens to explain both program fragility and sustained performance across institutional and geographical gradients spanning local, national, and global contexts.